2018
DOI: 10.21059/buletinpeternak.v42i2.30385
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical and Microbiological Qualities of Pegagan Duck Meat Preserved with Different Concentrations of Liquid Smoke and Storage Period

Abstract: The aim of this research was to investigate the quality of physicochemistry and microbiology of Pegagan duck meat preserved with various concentrations of liquid smoke and storage time. This study used a complete randomized design (CRD) with a 4x2 factorial pattern. The first factor was the concentration of liquid smoke solution consisted of 4 levels, namely 2; 4; 6, and 8% (v/v). The second factor was the storage time which includes 2 levels ie 12 and 24 hours. The replication used was 4 times. The observed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…The decrease in antioxidant activity may be attributed to the retard oxidative process. This result agrees with [66], who reported that during storage antioxidant activity decreased. Total phenolic compounds (TPC) and antioxidant activity were gradually decreased in all treatments and the lowest levels were observed at 6 months of storage those reported by [67].…”
Section: Effect Of Ls or Teo On Antioxidant Activity Of Chicken And T...supporting
confidence: 93%
See 1 more Smart Citation
“…The decrease in antioxidant activity may be attributed to the retard oxidative process. This result agrees with [66], who reported that during storage antioxidant activity decreased. Total phenolic compounds (TPC) and antioxidant activity were gradually decreased in all treatments and the lowest levels were observed at 6 months of storage those reported by [67].…”
Section: Effect Of Ls or Teo On Antioxidant Activity Of Chicken And T...supporting
confidence: 93%
“…The reason for decrease in antioxidant activity during storage may be attributed to possible oxidation of antioxidant components under favorable conditions during storage such as temperature and duration of storage [65]. The phenol compounds are volatile, the amount of phenol in meat decreases with time as a result of evaporation those reported by [66].…”
Section: Effect Of Ls or Teo On Phenolic Compounds Of Chicken And Tur...mentioning
confidence: 99%
“…The highest loss of water holding capacity was observed after 12 days of storage periods, with a significant effect (p<0.05) for chicken and turkey meatballs. The abovementioned findings are consistent with those obtained by Yosi et al (2018) who found that during the storage process, anaerobic glycolysis occurs, causing the meat's capacity to bind water to decrease, resulting in more water escaping the meat. Hegazy (2004) reported that the decreased of water holding capacity during storage might be attributed to protein denaturation and losses in protein solubility.…”
Section: Effect Of Liquid Smoke or Thyme Essential Oil On Water Holdi...supporting
confidence: 91%